Local causes of overcrowding in an emergency hospital in Sergipe (Research, Society and Development, 2021)
Overcrowding is a globally present problem that plagues the most diverse countries and public health services, thus, identifying its causes is a challenge for managers and government leaders. Therefore, this study aimed to describe the main local causes of overcrowding in an emergency service in the state of Sergipe. Some of the steps taken to get there were conceptualizing overcrowding in emergency hospital services and presenting the main causes of overcrowding, describing the characteristics of the service studied as well as pointing out its statistical overcrowding data, comparing these data with the causes presented and, therefore, the possible cause for overcrowding. For this purpose, documentary research was used as a method for data collection, through the study of statistical data against theoretical references about the overcrowding of Emergency Hospital Services and its causes and data published for DataSus. From the data analysis, it was possible to identify some causal factors that trigger overcrowding in the studied service. There was a large influx of patients to the service, as well as a high average length of stay due to the scarcity of resources to meet the service's demand. Finally, through the entire study carried out and the data presented, it was possible to identify that overcrowding in the service studied has multifactorial causes and there is a need for further investigation. Thus, it is necessary to encourage more research and improve the availability of data for analysis.